2017
DOI: 10.1039/c6cc09379e
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of alternating peptides exploiting a new polymerization technique based on Ugi's 4CC reaction

Abstract: We developed a one-pot synthetic technique for alternating peptides. Central to this technique is a new, catalyst-free polymerization based on Ugi's 4CC reaction. The treatment of imines with the ambident molecules bearing both an isocyanide and a carboxylic acid afforded alternating peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 45 publications
1
59
0
Order By: Relevance
“…The polymer structure was confirmed by 1 H NMR, 13 C NMR, and IR spectra (see Supporting Information). It is noted that the broadenings in the 1 H NMR spectrum are attributed to the proximity of noncontrolled chiral centers and the existence of cis‐trans rotamers of the amide bonds . We found that the reactivity of the benzyl group was quite low.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…The polymer structure was confirmed by 1 H NMR, 13 C NMR, and IR spectra (see Supporting Information). It is noted that the broadenings in the 1 H NMR spectrum are attributed to the proximity of noncontrolled chiral centers and the existence of cis‐trans rotamers of the amide bonds . We found that the reactivity of the benzyl group was quite low.…”
Section: Resultsmentioning
confidence: 74%
“…Table 1 shows the screening of benzylic‐protecting group and the results of deprotection reactions. We started from N ‐benzyl‐protected Poly(Gly‐Val) (entries 1 and 2), because we have already developed the synthetic method of the polymer . The polymer structure was confirmed by 1 H NMR, 13 C NMR, and IR spectra (see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations